Pengaruh Keseimbangan Kehidupan Kerja (Worklife Balance) dan Kepuasan Kerja terhadap Komitmen Organisasi pada Karyawan Rumah Sakit Erni Medika Jambi - Sari, Dita Febriana; Wahyudi, Bayu; Efawati, Yen (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The increasing complexity of work demands in hospital environments often leads to challenges in balancing professional and personal responsibilities, potentially impacting employees' organizational commitment. This study aims to examine the influence of work-life balance and job satisfaction on organizational commitment among employees of Erni Medika Hospital Jambi. Employing a quantitative approach with a causal associative design, data were collected from all 84 employees through structured questionnaires. The research instruments were tested for validity and reliability. Data analysis was conducted using multiple linear regression with SPSS version 30. The results revealed that both work-life balance and job satisfaction had a positive and significant impact on organizational commitment, both partially and simultaneously. The coefficient of determination (R²) indicates that 53.9% of the variation in organizational commitment can be explained by the two independent variables. These findings highlight the importance of implementing structured work-life balance policies and enhancing job satisfaction to strengthen employee commitment. In alignment with national health regulations, such as Law No. 17 of 2023 and Government Regulation No. 28 of 2024, hospitals are encouraged to improve employee welfare and performance-based recognition systems. Managers should also promote open communication to help employees manage their responsibilities effectively. This study provides practical implications for hospital management in fostering a more committed and satisfied workforce.